Modified needle drainage. A safe and efficient technique of subretinal fluid drainage in scleral buckling procedure. - Azad Rajvardhan; Kumar Ashok; Sharma Yog; Rajpal (Indian Journal of Ophthalmology, 2004)
PURPOSE: To compare modified needle drainage (MND) with conventional drainage (CD) of subretinal fluid (SRF) as described by Schepens in surgery for primary rhegmatogenous retinal detachment. METHODS: Prospective randomised clinical trial of 80 patients undergoing scleral buckling with subretinal fluid drainage for primary rhegmatogenous retinal detachment. In 40 patients modified needle drainage of subretinal fluid (SRF) was done using a perpendicular trans-scleral entry with a 26-gauge needle and the appearance of SRF in the hub of needle as end point. In 40 patients conventional drainage was done as described by Schepens using a diathermy needle. Adequacy of SRF drainage, intraoperative complications, anatomical and functional outcome were noted. RESULTS: 100% adequate drainage was achieved in all cases. The complication rate was 32.5% (n=13) in the CD group and 15% (n=6) in the MND group. In the CD group, 17.5% (n=7) patients had subretinal haemorrhage and in 2 eyes it was clinically significant. In the MND group 15% (n=6) of cases had subretinal haemorrhage and in one patient it was clinically significant. In the CD group, more serious SRF drainage complications were observed; these were absent in the MND group. CONCLUSION: Modified needle drainage is a safe and effective procedure for SRF drainage. In comparison with CD, MND is technically easy, less cumbersome and requires no special equipment.